Exploring healthcare workers’ perceptions and experiences regarding post-traumatic stress disorder after 2 years of the last global pandemic - Maryam Khazaee-Pool; Tahereh Pashaei; Fereshteh Yazdani; Koen Ponnet (BMC Health Services Research)
Abstract Background The adverse mental health consequences of the coronavirus epidemic for healthcare workers (HCWs) affect the quality of care and patient satisfaction; HCWs need to maintain good mental health during and after an epidemic, especially in low-income countries like Iran, where human resources in the health care sector are insufficient. The aims of this study are to explore the perceptions and experiences of healthcare workers regarding post-traumatic stress disorder (PTSD) after 2 years of the last Global Pandemic. Methods We conducted the present study in Mazandarn province, Iran, using a qualitative approach based on conventional content analysis. Participants were Iranian healthcare workers (HCWs) aged 30 and above, all with a history of post-traumatic stress disorder (PTSD) symptoms. Eligible candidates were selected through both purposive sampling (with maximum variation) and snowball sampling to ensure diversity in demographic characteristics and lived experience of phenomena. Data were collected through in-depth, semi-structured interviews, continuing until data saturation was reached. The interviews were analyzed using MAXQDA10 software, following the conventional content analysis approach as outlined by Graneheim and Lundman. Results Our analysis yielded five main themes and 18 categories: [1] Helplessness, including six categories: physical consequences, psychological reactions, feeling of guilt, job-related consequences, social consequences, and lack of support; [2] poor risk management, encompassing four categories: inadequate vocational skills training, poor anger management, low sense of security, and hazardous work environments; [3] life and death experience, with two categories: hopelessness about life and the future, and witnessing unexpected deaths; [4] seeking support, comprising three categories: social support, psychological support, and organizational support, and [5] self-care, involving three categories: personal responsibility for health, maintaining a healthy lifestyle, and building resilience against PTSD. Conclusion Our findings reveal a concerning picture of the mental health status of Iranian HCWs, particularly regarding the impact of the most recent pandemic. Many participants reported significant symptoms of stress, depression, anxiety, and PTSD, all of which profoundly affect their overall well-being. The most prominent themes identified were feelings of helplessness, inadequate risk management, encounters with life-and-death situations, and insufficient support systems. Alarmingly, several HCWs expressed intentions to leave their current positions or exit the healthcare profession altogether. Such trends pose a serious threat to the stability of Iran’s healthcare system. Consequently, proactive, solution-oriented strategies must be developed—both at the national level and in collaboration with international stakeholders—to mitigate the ongoing healthcare workforce shortage in Iran and address the broader global risk of healthcare service disruption.